CRISPR-Based Functional Genomics in Antiviral Innate Immune Response - Magdi A. Ali; Mohamed Zakaria El-Sayed; Wijdan Alomaim (Journal of Biomedicine and Biochemistry, 2025)
CRISPR (clustered regularly interspaced short palindromic repeats)-based genome-wide functional genomics can be applied to uncover novel genes controlling an antiviral immune response, thereby augmenting antiviral immunity. To date, much progress has been made in understanding the host and viral factors influencing the antiviral immune response since its discovery. However, many of the contributing genetic factors for the an- tiviral response remain uncharacterized. Using antiviral innate immu- nity as a model, this study reports the first genome-wide functional ge- nomic approach using an integrated lentivirus CRISPR-based gene knock- out (GeCKO) screening library to identify critical genetic factors influenc- ing the antiviral immune response. This functional CRISPR-based genomic regime is intended to enhance the understanding of genes and pathways controlling an antiviral immune response and broaden the use of CRISPR methodologies in antiviral research for therapeutic innovations. The scope of this study is to answer critical questions regarding how innate immunity fights off viral infections. Two hypotheses are investigated experimentally that key genetic factors influencing the immune induction of the interferon response remain to be found and perturbation of the interferon response will reveal a network of previously uncharacterized genes and pathways controlling an antiviral immune response. With systemic and comprehen- sive efforts to dissect the host-virus molecular arms race, a more nuanced understanding of the host antiviral response will be acquired, including the discovery of novel genes and pathways involved in antiviral immunity.